Multigram-Scale Synthesis of a gem-Difluoro-Substituted 4,5,6,7-Tetrahydrobenzo[c]thiophen-4-one Heterocycle via Oxidative Chlorination and Radical Smiles Rearrangement - Henry, Martyn C.; Anderson, Jack Q.; Jamieson, Craig (Synlett, 2023)
We report an optimized synthetic route towards a functionalized 4,5,6,7-tetrahydrobenzo[c]thiophene heterocycle bearing a gem-difluoromethylene moiety in 4 steps with an overall yield of 43%. The CF2 fragment was incorporated using a building block approach, by coupling an appropriate fluorinated alcohol with a C-3 sulfonyl chloride, synthesized via oxidative chlorination of an exocyclic benzyl thioether. Visible-light-mediated Smiles rearrangement of the resulting fluorosulfonate ester then furnishes the desired fluorinated thiophene scaffold.
Keywords: gem-difluoromethylene; fluorinated building blocks; heterocycles; 4,5,6,7-tetrahydrobenzo[c]thiophen-4-one; radical Smiles rearrangement